DEVELOPMENT OF COMMUNICATIVE SKILLS OF FUTURE PRIMARY SCHOOL TEACHERS - Zukhro IZBOSAROVA (Scholar Express Journal, 2023)
This article talks about these aspects and focuses on one of today's topical topics, that is, the aspects and effectiveness of the formation of communicative abilities of future elementary school teachers. The future primary class is covered based on the problem of professional characteristics of teachers, the process of professional training, pedagogical skills.
Keywords: Ability; communicative and pedagogical skills; training; communication